Preparation and mechanical performance of small-diameter PHBHHx vascular graft by electrospinning. Issue 10 (3rd July 2019) - Gao, Jing; Guo, Huiwen; Tian, Shunzhu; Qiao, Yansha; Han, Jiarui; Li, Yuling; Wang, Lu
Abstract: The straight and corrugated PHBHHx (Poly(3-hydroxybutyrate-co-3-hydroxhexanoate)) vascular grafts with 6 mm inner diameters were prepared successfully by electrospinning. Moreover, their mechanical behaviors were investigated compared with the commercial vascular grafts (SW-ePTFE woven). Electrospun PHBHHx fibers had a submicron scale. Straight grafts and SW-ePTFE grafts exhibited higher Young's modulus and tensile breaking strength in the circumferential direction than the corrugated grafts, but the break and elastic recovery rate were lower. Both the straight and corrugated samples had lower suture strength than the SW-ePTFE samples, but still satisfied the requirement of transplantation of small diameter vascular. The compliance of corrugated grafts was similar to SW-ePTFE grafts and lower than straight grafts. The results of hemolytic and cytotoxicity tests demonstrated that both the straight and corrugated grafts had good hemocompatibility and no cytotoxicity. Therefore, the results of this study showed the potential application of electrospun PHBHHX vascular grafts as small diameter vascular grafts. Graphical Abstract: